(untitled) (Global Journal of Human-Social Science, 2022)
In this article we contrast the concepts of affective development and emotional intelligence and we relate the first to a dynamic view of psychic life and the second to an atomistic and compartmentalized view We provide various empirical evidence to support this statement In the first of these pieces of evidence it is shown that the interaction between affects and cognition manifested through affective bonds is subject to evolution while the second shows that the behavior of affects emotions as they are commonly called in specialized literature is erratic and non-progressive throughout the lives of individuals From this evidence it follows that the exclusive education of emotions does not lead by itself to a harmonic maturation of individuals since it does not respond naturally to progressive improvement or growth From the latter it follows that the interaction between the cognitive and the affective must be taken into account in order to achieve authentic maturation and not resort to addressing emotions in isolation and without paying attention to the fact that affects act in interaction with the so-called processes cognitive This work also insists on the need to resort to a global explanatory theory of affectivity whose application would improve the results obtained with the techniques that use the currents of so-called emotional intelligence and or education